(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Background radiation involves the measure of the level of ionizing radiation present in the environment at a particular location. This research seek to generate data of the natural background radiation level of some selected Sections at Kabba College of Agriculture, using RadEye G20 survey meter. A total of 15 sections of the College were randomly selected and the background radiation dose rate of the sections were measured. The indoor dose rate ranged from (0.09 â€“ 0.13) ðœ‡Sv/yr, while the outdoor dose rate ranged from (0.07 - 0.10) ðœ‡Sv/yr. The indoor annual effective dose were observed to be greater than the outdoor annual effective dose in all the College Sections measured. The lowest total annual effective dose 0.75 ð‘šð‘†ð‘£/ð‘¦ð‘Ÿ was found at the Academic staff block. The highest total annual effective dose of 1.09 ð‘šð‘†ð‘£/ð‘¦ð‘Ÿ was found at the livestock building, this might be due to the high-altitude nature of the area and the rocky materials used in the construction of the building. The highest total annual effective dose of the study area was slightly above the recommended limit of 1.0 ð‘šð‘†ð‘£/ð‘¦ð‘Ÿ. The result obtained from this research may not constitute immediate health risk to the staff and student of the college